2020
DOI: 10.2147/jpr.s231737
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypnosis Associated with 3D Immersive Virtual Reality Technology in the Management of Pain: A Review of the Literature</p>

Abstract: Hypnosis is well documented in the literature in the management of acute and chronic pain. Virtual reality (VR) is currently gaining credibility in the same fields as hypnosis for medical applications. Lately, the combination of hypnosis and VR was considered. The aim of this scoping review is to understand the current studied contexts and effects of virtual reality hypnosis (VRH) for the management of pain. We searched on PubMed, Taylor & Francis Online, and ProQuest databases with the following terms: "virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 52 publications
1
40
0
1
Order By: Relevance
“…Interestingly, the suggestions for analgesia have been found effective also in healthy mediums undergoing nociceptive stimulation (Fidanza et al, 2017 ) and in chronic pain patients independently from hypnotizability (Elkins et al, 2007 ; Jensen, 2011 ; Jensen and Patterson, 2014 ; Mazzola et al, 2017 ; Facco et al, 2018 ; Sandvik et al, 2020 ). This can be accounted for by expectation of/motivation to analgesia (Milling et al, 2005 ; Krystek and Kumar, 2016 ; Montgomery et al, 2018 ; Perri et al, 2020 ) leading to placebo responses (Benedetti, 2013 ) which can reduce pain and pain-related psychological symptoms in the general population (Liossi et al, 2006 ; Brugnoli, 2016 ; Wortzel and Spiegel, 2017 ; Rousseaux et al, 2020 ). Thus, suggestions may induce non opioid analgesia in highs, opioid placebo responses in lows and, probably, mixed reactions in mediums.…”
Section: Suggestions For Analgesiamentioning
confidence: 99%
“…Interestingly, the suggestions for analgesia have been found effective also in healthy mediums undergoing nociceptive stimulation (Fidanza et al, 2017 ) and in chronic pain patients independently from hypnotizability (Elkins et al, 2007 ; Jensen, 2011 ; Jensen and Patterson, 2014 ; Mazzola et al, 2017 ; Facco et al, 2018 ; Sandvik et al, 2020 ). This can be accounted for by expectation of/motivation to analgesia (Milling et al, 2005 ; Krystek and Kumar, 2016 ; Montgomery et al, 2018 ; Perri et al, 2020 ) leading to placebo responses (Benedetti, 2013 ) which can reduce pain and pain-related psychological symptoms in the general population (Liossi et al, 2006 ; Brugnoli, 2016 ; Wortzel and Spiegel, 2017 ; Rousseaux et al, 2020 ). Thus, suggestions may induce non opioid analgesia in highs, opioid placebo responses in lows and, probably, mixed reactions in mediums.…”
Section: Suggestions For Analgesiamentioning
confidence: 99%
“…Although hypnosis and VR are well documented in the literature, a few studies used the combination of both (VRH) or compare them in their protocol. We recently identi ed 8 studies about VRH and pain that showed VRH as useful for pain and anxiety reduction in different clinical settings such as chronic pain, burn pain and physical trauma (26). However, most of the investigations are case studies and results about VRH and pain did not show consistent e cacy for all patients all the days (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…This tool is today known as virtual reality hypnosis (VRH) (23). Although VRH showed is effectiveness in the management of anxiety and pain in different medical contexts such as physical trauma, chronic pain management or intensive care units (12,(24)(25)(26), to our knowledge, VRH has not yet been used during pre and postoperative cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The Rationale for Using Hypnosis in the Treatment of Obesity Hypnosis has been successfully used as an anti-stress and relaxation strategy to treat many chronic conditions exacerbated by negative emotions and social factors (e.g., quitting smoking [30]), chronic digestive diseases [31], cancerrelated symptoms in palliative care setting [32], acute and chronic pain [33]. Individuals can practice hypnosis on their own (self-hypnosis); hypnotherapy (either alone or in addition to other psychotherapies, such as cognitive-behavioral techniques) has been involved in the obesity multidimensional approach to increase self-control, to improve exercise levels, to boost self-esteem, and to strengthen motivation in changing eating habits [34].…”
Section: History and Definitionsmentioning
confidence: 99%